2023
DOI: 10.1021/acs.inorgchem.3c00710
|View full text |Cite
|
Sign up to set email alerts
|

Decorating an Anticuboctahedral Copper Kernel with Labile Surface Coatings for Controlling Optical and Catalytic Properties

Abstract: Manipulating the interfacial/surface structure of ligand-stabilized atomically precise metal nanoclusters (NCs) is one of the central tasks in nanoscience because surface motifs are directly related to key properties of nanomaterials. Although great progress has been made in engineering the surface of gold and silver nanoclusters, parallel studies on lighter copper analogues hitherto remain unexplored. In this work, we report the design, synthesis, and structure of a new class of copper nanoclusters featuring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 71 publications
1
6
0
Order By: Relevance
“…1c and d). This structural architecture was previously reported by Sun et al 40 In contrast to another reported Cu 29 NC (Cu 29 -Adm NC) with adamantane thiolate (–SAdm), we observe a difference in the connecting chlorides (Fig. S7†).…”
Section: Resultssupporting
confidence: 77%
“…1c and d). This structural architecture was previously reported by Sun et al 40 In contrast to another reported Cu 29 NC (Cu 29 -Adm NC) with adamantane thiolate (–SAdm), we observe a difference in the connecting chlorides (Fig. S7†).…”
Section: Resultssupporting
confidence: 77%
“…In consideration of the high abundance, low price, low environmental footprint, and unique catalytic properties of copper, great interest has been sparked for copper nanoclusters in recent years. ,,,,,,,,, Several groups of Liu, Bakr, Zang, Sun, Hyeon, Hayton, and Zheng have successfully crystallized out a handful of copper nanoclusters by advanced synthetic strategies, which include [Cu 20 H 11 (S 2 P­(O i Pr) 2 ) 9 ], [Cu 32 H 20 {S 2 P­(O i Pr) 2 } 12 ], [Cu 23 (PhSe) 16 (Ph 3 P) 8 (H) 6 ] + , [Cu 61 (S t Bu) 26 S 6 Cl 6 H 14 ], Cu 8 (H)­(L1) 6 (L1 = 9 H -carbazole-9-carbodithioate), Cu 18 H­(PET) 14 (Ph 3 P) 6 (NCS) 3 (PET = phenylethanethiolate), [Cu 36 H 10 (PET) 24 (PPh 3 ) 6 Cl 2 ], [Cu 20 (CCPh) 12 (OAc) 6 )], [Cu 25 H 22 (PPh 3 ) 12 ]­Cl, and [Cu 25 H 10 (SPhCl 2 ) 18 ] 3– . ,,,,,,,,, The atomically precise copper nanoclusters are highly active, enabling driving a family of chemical reactions under mild conditions. The well-documented copper nanocluster for organic catalysis refers to Cu 6 H 6 (PPh 3 ) 6 , which is promising in conjugate reduction reactions. , In several pioneering reports, copper nanoclusters have also been used as catalysts for driving thermal catalysis (click chemistry and hydrogenation of ketones), electrocatalysis (CO 2 reduction), and photocatalysis (C–N Coupling and CO 2 reduction). ,, Notably, the key role of surface coordination ligands in controlling the catalytic performance has also been observed in copper cluster nanocatalysts . To gain insights into the underlying mechanism of the “ligand effect” and help control the copper cluster catalysis, it is thus desirable to obtain isostructural copper nanoclusters for direct structural and catalytic comparison.…”
Section: Introductionmentioning
confidence: 99%
“…Fortunately, metal nanoclusters have emerged as a swiftly advancing category of nanomaterials characterised by their atomically precise structures and diverse applications. 14–29 Furthermore, the morphology of metal nanoclusters, such as metal–metal bonds and metal–ligand interactions, can be precisely controlled through ligand exchange, 30–35 metal doping, 36–40 and other techniques. 41,42 Most importantly, single-crystal X-ray diffraction enables us to obtain atomic-level interface information, including the arrangement of doped metals within nanoclusters and the bonding modes between peripheral ligands and metals.…”
mentioning
confidence: 99%